PESAN MORAL DALAM NOVEL “PULANG” KARYA TERE LIYE - Dian Anggreaini; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The work of literature can be interpreted as prose narrative that isimaginative. As a media, novel is one of the work of literature that can be used todeliver a message or value from a work. The moral value who is delivered by thewriter in a fiction work is certainly so beneficial and useful. One of the famouswriter in this country is Tere liye with the variety of his best seller novel, such asnovel Pulang which has an increasing in ordering printed edition untill two dozentimes since it is published on September 2015 untill January 2016. This is whatmake the author want to know “The Moral Value inThe Novel Pulang by TereLiye”.The method of this reasearch is qualitative which use narrative analysisVladimir Propp and Tzvetan Todorov. The subject of this research is novelPulang by Tere Liye. This research is focused on the problem which regard withanalysis of the moral value. The way of collecting the data is done by thetechnique of documentation and the library study. After collecting the data,Analysis from this research method will be done to get the result.The result of this research will show the moral value that is gotten by thecharacters and the plot of the story, there are some categories of moral valuewhich cover the moral message in the human relationship with God and acceptthe destiny, that all happened cannot be changed. As a human, it just can choosefor receiving or rising and trying to come forward. In a human relationship withhimself on loyality to family, the principle and commitment which makes theestablishment of a service to something. And the relationship between the otherhuman there is love each other that make the attitude of devotion, help each other,kinship, and caring.Keywords : Moral Value, Novel Pulang Tere Liye, Narrative Analysis